Dynamic Simulation and Optimization of an Off-grid Solar Photovoltaic Driven Drinking Fountain with Battery Storage - Roberta P. S. Souza; Luis G. G. K. Gesteira; Antonio G. S. Almeida (International Journal of Smart Grid and Sustainable Energy Technologies, 2021)
This paper presents a case study involving the design and energy saving analysis of an off-grid solar photovoltaic driven drinking fountain with battery storage. A dynamic simulation in TRNSYS software is performed to model and evaluate the transient processes occurring in this renewable system. A sensitivity analysis of the main design parameters, power generation capacity and electric storage capacity, was performed in order to optimize the scheme. The case study was carried out at Federal Institute of Education, Science and Technology of Bahia in Salvador, in the northeast of Brazil. The temperature profiles and electrical energy flows of the optimized system are investigated by means of a daily, weekly and yearly analysis. The outcomes achieved show that the optimized system showed a 33.3% increase in thermal efficiency and 15.1 % increase in the global efficiency in relation to the base case. This system was able to produce 5932.7 L of chilled water per year and a 65626.8 Wh reduction of primary energy consumption per year. This study can be applied to universities, schools or places with large flow of people.